PRODUCTION OF INDUSTRY SALT WITH SEDIMENTATION – MICROFILTRATION PROCESS: OPTIMAZATION OF TEMPERATURE AND CONCENTRATION BY USING SURFACE RESPONSE METHODOLOGY - Widayat Widayat (TEKNIK, 2009)
The salt of sodium chloride commonly used consumption in house , so as a raw material in industry. Thequality of salt depends on sodium chloride concentration. The objective of this research is obtained ofoptimum condition in production of salt industry by using sedimentation and microfiltration process. Theoptimization used surface response methodology and analysis by Statistica 6 software. The responseperceived is NaCl concentration in product. The experiments do by mixing stearic acid with NaOH solutionto product stearic sodium. Then, the solution mixed with sea water, so the white solid will be emerge, thereare stearic calcium and stearic magnesium. And so filtrate evaporated until to obtain salt. TheMathematical model for reduction of Ca2+ and Mg2+ are1 222 221 1 Y = 93,3185 + 1,0967 X + 0,1909 X +1,0682 X - 0,2333 X - 0,3376 X X , with maximum conversion is94,46% at temperature 82,42oC and stearic sodium concentration 14,16%(v/v). The maximum of NaClconcentration is 96,19% at temperature 81,54oC and stearic sodium concetration 13,11 %(v/v). Themathematical model for NaCl production is1 222 221 1 Y = 92,7596 - 0,3443 X - 3,3706 X + 2,9553 X - 0,9562 X - 1,9272 X X . The results of NaCl not yetfulfilled with SNI industry salt. The NaCl concetration in SNI is 98,5%. So, this process is nt aplicable forproductiob salt industry in Indonesia.